Blazing my golden journey (1960-2010) : through the seed route : commemorative book - Chin, H.F. (2010)
This commemorative book is a tribute to the fifty years of service and contribution to agriculture of Dr Chin Hoong Fong, Bioversity International Honorary Fellow and Professor Emeritus of the Universiti Putra Malaysia. The book highlights his observations and experiences as a highly respected teacher and an internationally renowned seed scientist. Professor Chin pioneered storage of recalcitrant seeds in 1970s and has served in numerous national and international committees, including the Board of Trustees of the International Board on Plant Genetic Resources (now Bioversity International) and the Committee of the Svalbard Global Seed Vault.